Effects of subjective and objective autoregulation methods for intensity and volume on enhancing maximal strength during resistance-training interventions: a systematic review - Larsen, S.; Kristiansen, E.; van den Tillaar, R. (PeerJ, 2021)
Background: Maximal strength is a critical determinant of performance in numerous sports. Autoregulation is a resistance training prescription approach to adjust training variables based on the individuals` daily fluctuations in performance, which are a result of training-induced fitness and fatigue, together with readiness from daily non-training stressors.